Citizen K [videorecording (DVD)] - Gibney, Alex; Gibney, Alex; Gibney, Alex; Gibney, Alex; Khodorkovskiĭ, Mikhail, 1963- (Kino Lorber, 2020)
Profiles Mikhail Khodorkovsky, a former Russian oligarch and prisoner who became a political dissident speaking out against the Putin regime, and explores the relationship between oligarchy and government and its effect on democracy.